A Modified Rabbit Ulna Defect Model for Evaluating Periosteal Substitutes in Bone Engineering: A Pilot Study - El Backly, Rania M.; Chiapale, Danilo; Muraglia, Anita; Tromba, Giuliana; Ottonello, Chiara; Santolini, Federico; Cancedda, Ranieri; Mastrogiacomo, Maddalena (Frontiers in Bioengineering and Biotechnology, 2015)
The present work defines a modified critical size rabbit ulna defect model for bone regeneration in which a non-resorbable barrier membrane was used to separate the radius from the ulna to create a valid model for evaluation of tissue-engineered periosteal substitutes. Eight rabbits divided into two groups were used. Critical defects (15 mm) were made in the ulna completely eliminating periosteum. For group I, defects were filled with a nanohydroxyapatite poly(ester urethane) scaffold soaked in PBS and left as such (group Ia) or wrapped with a tissue-engineered periosteal substitute (group Ib). For group II, an expanded-polytetrafluoroethylene (e-PTFE) (GORE-TEX®) membrane was inserted around the radius then the defects received either scaffold alone (group IIa) or scaffold wrapped with periosteal substitute (group IIb). Animals were euthanized after 12–16 weeks, and bone regeneration was evaluated by radiography, computed microtomography (μCT), and histology. In the first group, we observed formation of radio-ulnar synostosis irrespective of the treatment. This was completely eliminated upon placement of the e-PTFE (GORE-TEX®) membrane in the second group of animals. In conclusion, modification of the model using a non-resorbable e-PTFE membrane to isolate the ulna from the radius was a valuable addition allowing for objective evaluation of the tissue-engineered periosteal substitute.